(untitled) (Stavební obzor - Civil Engineering Journal, 2021)
This research revealed the crack generation of the highway embankment from the water losing shrinkage of the wet black cotton soil (BCS), which is a type of soil with high swell-shrink potential. The road seepage meter was used to test the permeability of filling materials, which was used to replace BCS. The moisture content and embankment deflection of BCS foundation were measured after the rainy season. Based on the coupled consolidation theory for unsaturated soil, the change in additional tension stress of the embankment induced by water loss shrinkage of BCS was simulated by Abaqus. The results indicated that the rainfall seeped into the foundation through highly permeable refill materials to result in BCS expansion and decrease the embankment strength. After the rainy season, the additional tensile stress caused by water loss shrinkage of BCS induces cracking of highway embankment, and the maximum cracking depth often appears at the shoulder of highway. The deep and wide cracks are easy to appear in the low embankment constructed on a thick BCS foundation under strong evaporation.